Comparison of Endothelium-Related Responses to Nucleotides of Dog and Monkey Cerebral Arteries - Ayman Geddawy; Takashi Shimosato; Masashi Tawa; Takeshi Imamura; Tomio Okamura (Elsevier, 2010)
We compared mechanical responses to uridine-5'triphosphate (UTP) and 2-(methylthio)adenosine-5'diphosphate (2MeSADP) of cerebral arteries isolated from dogs and monkeys. In the dog, UTP induced endothelium-independent contraction, whereas 2MeSADP induced endothelium-dependent relaxation that was abolished by NG-nitro-l-arginine (l-NA). In the monkey, both UTP and 2MeSADP induced endothelium-dependent relaxation.l-NA largely inhibited the UTP-induced relaxation whereas it partially inhibited the 2MeSADP-induced relaxation, and both remaining relaxations were abolished by charybdotoxin plus apamin. In conclusion, dog and monkey cerebral arteries respond differentially to UTP and similarly to 2MeSADP; however, involvement of endothelium-derived relaxing factor in the endothelium-dependent relaxation by 2MeSADP is quite different between the two species. Keywords:: cerebral artery, endothelium-dependent relaxation, nucleotide